2009
DOI: 10.1016/j.ffa.2009.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Reversed Dickson polynomials over finite fields

Abstract: Reversed Dickson polynomials over finite fields are obtained from Dickson polynomials D n (x, a) over finite fields by reversing the roles of the indeterminate x and the parameter a. We study reversed Dickson polynomials with emphasis on their permutational properties over finite fields. We show that reversed Dickson permutation polynomials (RDPPs) are closely related to almost perfect nonlinear (APN) functions. We find several families of nontrivial RDPPs over finite fields; some of them arise from known APN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 13 publications
0
66
0
Order By: Relevance
“…In [3], Hou et al discussed some connections between reversed Dickson PPs of F q and APN functions of F q , and obtained several families of reversed Dickson PPs. Throughout the reminder of this article, unless specified, p is always assumed to be an odd prime.…”
Section: Reversed Dickson Polynomials Of the Second Kindmentioning
confidence: 99%
See 2 more Smart Citations
“…In [3], Hou et al discussed some connections between reversed Dickson PPs of F q and APN functions of F q , and obtained several families of reversed Dickson PPs. Throughout the reminder of this article, unless specified, p is always assumed to be an odd prime.…”
Section: Reversed Dickson Polynomials Of the Second Kindmentioning
confidence: 99%
“…and E n (x, a) := On the other hand, Hou, Mullen, Sellers and Yucas [3] introduced the definition of the reversed Dickson polynomial of the first kind, denoted by D n (a, x), as follows…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [5], it was shown that the reversed Dickson polynomials of the first kind are closely related to Almost Perfect Nonlinear (APN) functions which have applications in cryptography. Hou and Ly found more properties of the reversed Dickson polynomials of the first kind and necessary conditions for them to be a permutation of F q ; see [4].…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by [1], [2], [3], [4], and [5], we fix k and study the general properties and permutation property of the reversed Dickson polynomials of the (k + 1)-th kind over finite fields. The results obtained in this paper unify and generalize many existing results on reversed Dickson polynomials.…”
Section: Introductionmentioning
confidence: 99%